Potential Mapping of Pesantren as Community Economic Empowerment Capital - Toni Priyanto; Muhammad Anwar Fathoni (Journal of Economics, Business, and Government Challenges, 2019)
The purpose of this research is to the identification and potential mapping as community economic empowerment capital. The method used is descriptive quantitative in order to get a deeper result. The object of this research is Pesantren in Cibadak Subdistrict, Lebak, Banten. Data collection technique used is primary data and secondary data. Data analysis techniques used is SWOT to analyze strengths, opportunities, weaknesses, and threats of economic potential in Pesantren. Based on the findings, Pesantren had sufficient capital in the economic development of the community, including public capital, educational competency capital, and capital of management pesantren. However assets, technology, and information capital owned by pesantren still low, there needs to be penetration from the government in the form of incentives to support the involvement of pesantren in economic empowerment.